2016
DOI: 10.1155/2016/9701574
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Interleukin-6 Is a Potential Prognostic Factor for Colorectal Cancer, including Stage II Patients

Abstract: Aims. To evaluate the prognostic significance of serum interleukin-6 (IL-6) in colorectal cancer (CRC). Patients and Methods. Preoperative serum IL-6 was measured in 233 CRC patients and 13 healthy controls. Relationships between IL-6 and various clinicopathological factors were evaluated, and the overall survival (OS) and disease-free survival (DFS) rates according to IL-6 status were calculated for all patients and according to disease stage. Results. The mean IL-6 level was 6.6 pg/mL in CRC patients and 2.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…Because of the use of chemical agents for carcinogenesis in the development of spontaneous tumour‐bearing mice, which might exert additional influences on hepatic CYP450s, we preferred s.c. transplanted tumour‐bearing mice in our study and further validated this mouse model from the perspective of drug metabolic enzyme kinetics considerations (Figure ). Similar to clinical reports (Baharlou et al, ; Schneider et al, ; Shiga et al, ; Yang et al, ), no significant inflammation was observed at the early stage of tumour bearing (Figure f). However, it was interesting to note that CYP3A had already been inhibited at this stage (Figure ).…”
Section: Discussionsupporting
confidence: 90%
“…Because of the use of chemical agents for carcinogenesis in the development of spontaneous tumour‐bearing mice, which might exert additional influences on hepatic CYP450s, we preferred s.c. transplanted tumour‐bearing mice in our study and further validated this mouse model from the perspective of drug metabolic enzyme kinetics considerations (Figure ). Similar to clinical reports (Baharlou et al, ; Schneider et al, ; Shiga et al, ; Yang et al, ), no significant inflammation was observed at the early stage of tumour bearing (Figure f). However, it was interesting to note that CYP3A had already been inhibited at this stage (Figure ).…”
Section: Discussionsupporting
confidence: 90%
“…It is assumed that adipose tissue produces different types of hormones and pro-inflammatory cytokines including IL-6, TNF-α, leptin and adiponectin, which could provide desirable micro-environmental inflammatory conditions for cancerous cells [22, 25]. Besides, it was shown that high levels of IL-23 and IL-10 in serum [29, 42] and IL-8 and IL-6 in the microenvironment are associated with progression of CRC [43–45]. Recent investigations have highlighted the role of IGF in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that adipose tissue produces different types of hormones and pro-inflammatory cytokines including IL-6, TNF-α, leptin and adiponectin, which could provide desirable micro-environmental inflammatory conditions for cancerous cells [22,25]. Besides, it was shown that high levels of IL-23 and IL-10 in serum [29,42] and IL-8 and IL-6 in the microenvironment are associated with progression of CRC [43][44][45]. Recent investigations have highlighted the role of IGF in CRC.…”
Section: Discussionmentioning
confidence: 99%